Ovarian expression, polymorphism identification and association of SIRT3 gene with reproduction traits in goats. Issue 5 (1st October 2021) - Silpa, M.V.; Naicy, T.; Aravindakshan, T. V.; Radhika, G.; Joan, J.; Jinty, S.
Abstract: The NAD + -dependent protein deacetylase, Sirtuin3 (SIRT3), plays a role in fertility by preventing the activation of reactive oxygen species (ROS). A novel study was conducted on caprine SIRT3, to study its ovarian expression, explore the sequence variability in exon 7 and analyze its association with prolificacy in two native goat breeds of Kerala, Malabari and Attappady Black. The mRNA isolated from ovaries of six Malabari and Attappady Black goats were subjected to quantitative PCR (qPCR) using GAPDH and β-actin as reference genes. Genomic DNA was isolated from 185 goats (99 Malabari and 86 Attappady Black) and subjected to PCR-SSCP to identify polymorphism in exon 7 of SIRT3 and association with litter size was analyzed. The ovarian expression of caprine SIRT3 was significantly higher ( p  ≤ 0.01) in Malabari than low prolific Attappady Black. PCR-SSCP analysis revealed, exon 7 of SIRT3 was polymorphic with three genotypes namely, AA, AB and BB with a novel SNP, g.154C > T in the 3′UTR. A significant association ( p  ≤ 0.05) was noticed between the genotypes of SIRT3 and litter size. The results obtained from this study highlight the role of SIRT3 in reproduction and hence SIRT3 may be considered as a potential candidate gene for genetic improvement in goats.